Centro de Día Adulto Mayor en Duitama Boyacá (2021)
The purpose of this research is to make known the importance of Day Care Centers for the elderly, since they are those facilities specialized in the care of the elderly who present some degree of physical (loss of weight, strength, energy, walking speed) or cognitive (Alzheimer's), sensory and mobility impairment, where they receive specialized care in order to prevent and rehabilitate such disorders.